Differential Evolution In Search of Solutions - Feoktistov, Vitaliy; SpringerLink (Online service) (Boston, MA : Springer US, 2006)
The human being aspires to the best possible performance. Both individuals and enterprises are looking for optimal$1 (Bin other words, the best possible$1 (Bsolutions for situations or problems they face. Most of these problems can be expressed in mathematical terms, and so the methods of optimization undoubtedly render a significant aid. In cases where there are many local optima; intricate constraints; mixed-type variables; or noisy, time-dependent or otherwise ill-defined functions, the usual methods don$1 (Bt give satisfactory results. Are you seeking fresh ideas or more efficient methods, or do you perhaps want to be well-informed about the latest achievements in optimization? If so, this book is for you. This book develops a unified insight on population-based optimization through Differential Evolution, one of the most recent and efficient optimization algorithms. You will find, in this book, everything concerning Differential Evolution and its application in its newest formulation. This book will be a valuable source of information for a very large readership, including researchers, students and practitioners. The text may be used in a variety of optimization courses as well. Features include: Neoteric view of Differential Evolution Unique formula of global optimization The best known metaheuristics through the prism of Differential Evolution Revolutionary ideas in population-based optimization Audience Differential Evolution will be of interest to students, teachers, engineers, and researchers from various fields, including computer science, applied mathematics, optimization and operations research, artificial evolution and evolutionary algorithms, telecommunications, engineering design, bioinformatics and computational chemistry, chemical engineering, mechanical engineering, electrical engineering, and physics.s
Differential Evolution -- Neoteric Differential Evolution -- Strategies of Search -- Exploration and Exploitation -- New Performance Measures -- Transversal Differential Evolution -- On Analogy with Some Other Algorithms -- Energetic Selection Principle -- On Hybridization of Differential Evolution -- Applications -- End Notes.
Keywords: Mathematics; Operations research; Decision making; Computer programming; Artificial intelligence; Algorithms; Mathematical optimization; Computational intelligence; Mathematics; Optimization; Artificial Intelligence (incl. Robotics).; Programming Techniques; Algorithms; Operation Research/Decision Theory; Computational Intelligence; Electronic books